2016
DOI: 10.2147/ijn.s97181
|View full text |Cite
|
Sign up to set email alerts
|

Rapid green synthesis of silver and gold nanoparticles using<em> Dendropanax morbifera</em> leaf extract and their anticancer activities

Abstract: Dendropanax morbifera Léveille is an oriental medicinal plant that is traditionally used in folk medicine and grows in a specific region of South Korea. We aimed to enhance the utilization of D. morbifera medicinal plants for synthesis of silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs). D. morbifera leaf extract acted as both a reducing and a stabilizing agent that rapidly synthesized Dendropanax AgNPs (D-AgNPs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(14 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The changes in color and appearance of the peak were due to the excitation of the SPR of Ag NPs and Au NPs. This particular analysis was confirmed and justified when a similar type of absorption spectrum was observed, which is obtained from the aqueous leaf extract of Dendropanax morbifera [18]. In another study, Mourato et al [19] reported UV-Vis spectra of biosynthesized Ag NPs and Au NPs are 550 nm 420 nm, which is close to our finding.…”
Section: Discussionsupporting
confidence: 91%
“…The changes in color and appearance of the peak were due to the excitation of the SPR of Ag NPs and Au NPs. This particular analysis was confirmed and justified when a similar type of absorption spectrum was observed, which is obtained from the aqueous leaf extract of Dendropanax morbifera [18]. In another study, Mourato et al [19] reported UV-Vis spectra of biosynthesized Ag NPs and Au NPs are 550 nm 420 nm, which is close to our finding.…”
Section: Discussionsupporting
confidence: 91%
“…In our experiments, synthesis of MA-AgNPs was carried out at RT thus saving energy. AgNP formation has been reported at ambient13 as well as at high temperatures 12. As most of our experiments on MA-AgNPs activities were carried out within a week of their synthesis, we evaluated the stability up to nine days.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, MSCs showed both concentration-and time-dependent absorption of NPs, with scarce impact on key MSC features and a dose-dependent cytotoxicity in lung and ovarian cancer cells both in vitro and in vivo (Sadhukha et al, 2014). In other studies, PLGA-PTX-or PLGA-DOX-loaded MSCs were found in different cancer types, like prostate, lung and glioma (Pacioni et al, 2015;Levy et al, 2016;Wang et al, 2016). In an orthotopic lung tumor model, Layek et al demonstrated that MSCs carrying PTX-loaded NPs homed to cancer tissues and created cellular drug storage that released the drug over the time.…”
Section: Mscs and Nanoparticlesmentioning
confidence: 56%